Pengaruh Kompensasi Manajemen dan Proporsi Dewan Komisaris Independen terhadap Tax Avoidance dengan Kepemilikan Institusional Variabel Pemoderasi - Nanda Rahmalya; Suciati Muanifah (Universitas Pamulang, 2023)
This study aims to determine the effect of management compensation and the proportion of independent commissioners on tax avoidance. With the moderating variable, namely institutional ownership. The sample for this research is industrial sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Using a purposive sampling method with a population of 50 companies and a research sample of 6 companies with observations for 5 (five) years, namely the 2017-2021 period. The results of the study prove that (1) Management Compensation and the Proportion of Independent Commissioners have a simultaneous effect on Tax Avoidance. (2) Management Compensation has no effect on Tax Avoidance. (3) The proportion of Independent Commissioners has no effect on Tax Avoidance. (4) Institutional Ownership weakens the relationship between Management Compensation and Tax Avoidance. (5) Institutional Ownership weakens the relationship between the Board of Commissioners' Proportion of Tax Avoidance.